Heritage in Song and Ritual: From Beshik Toyu to Baptism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article explores the role of folklore and folk songs in the rituals related to the birth of a child among Uzbeks, Kyrgyz, and Russians. It describes traditions such as "Beshik Toy" and "Beshikke Saluu," as well as Russian rituals of birth, reflecting cultural characteristics. The article analyzes common features of these rituals, including spiritual and religious elements, as well as the focus on protecting the newborn. It emphasizes the importance of these traditions in ensuring the health and well-being of infants, demonstrating both unity and differences in approaches to childbirth across different cultures.